2006
DOI: 10.1002/path.1928
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated expression of P1 and P2 promoter-driven hepatocyte nuclear factor-4α in the pathogenesis of human cancer

Abstract: Hepatocyte nuclear factor-4alpha (HNF4alpha) exists in multiple isoforms that are generated by alternative promoter (P1 and P2) usage and splicing. Here we establish monoclonal antibodies (mAbs) for detecting P1 and P2 promoter-driven HNF4alpha, and evaluate their expression in normal adult human tissues and surgically resected carcinomas of different origins. Using immunohistochemical analysis, we demonstrate that, while P1 promoter-driven HNF4alpha is expressed in hepatocytes, small intestine, colon, kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
231
2
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(255 citation statements)
references
References 46 publications
10
231
2
5
Order By: Relevance
“…However, in control experiments, they were detected in other tissues in which each was already known to be expressed (Sladek et al, 1990;Zennaro et al, 1997;Zineb et al, 1998;Tulachan et al, 2003;Jeyasuria et al, 2004;Tanaka et al, 2006). These results suggest that they are not expressed or expressed at a very low level in the cerebellum at this stage of development.…”
Section: Nuclear Receptors Expression Patterns In the P21 Cerebellummentioning
confidence: 74%
“…However, in control experiments, they were detected in other tissues in which each was already known to be expressed (Sladek et al, 1990;Zennaro et al, 1997;Zineb et al, 1998;Tulachan et al, 2003;Jeyasuria et al, 2004;Tanaka et al, 2006). These results suggest that they are not expressed or expressed at a very low level in the cerebellum at this stage of development.…”
Section: Nuclear Receptors Expression Patterns In the P21 Cerebellummentioning
confidence: 74%
“…Although two studies report the absence of P1 transcripts (27,32), one report suggests the expression of transcripts derived from the P1 promoter (33). However, it is noteworthy that the only study to examine isoformspecific HNF4A expression at the protein level detected only P2-derived isoforms in adult pancreas (35).…”
mentioning
confidence: 91%
“…The UC-MSCs were prepared as previously described. The mesenchymal tissue was diced into cubes of approximately 1 cm 3 . Following the removal of the supernatant fraction, the precipitate was washed with DMEM/F12 (Gibco) and centrifuged at 250£g for 5 min.…”
Section: Cell Culturementioning
confidence: 99%
“…1 Hepatocyte nuclear factor 4a (HNF4a) is a dominant transcriptional regulator of hepatocyte differentiation and hepatocellular carcinogenesis (HCC). 2,3 We have previously demonstrated that overexpression of HNF4a activates various hepatic-specific genes and enhances MSC differentiation.…”
mentioning
confidence: 99%